Comparative Study Between Malaysia and Nigeria’s Easement Law in Land Policy - Salihu, Rufai; Zulkifli, Fatimah binti Zulkifli; MohdFauzi, Mohamad Shafiq MohdFauzi; Ahmad, Busra binti Ahmad Razli (Research in Management of Technology and Business, 2023)
Malaysia National Land Code 1965 (NLC) provides several provisions to allow landowners to use other people’s land, especially neighboring land, for specific routes, such as obtaining access to public places. Nigeria’s Land Use Act, originally known as the Land Use Degree, was enacted on March 29, 1978, and is the primary legislation governing all existing land tenure. Each country has a particular legal provision to cater to implementing an easement. National Land Code 1965 (NLC) in Malaysia is the primary reference on easement definition, rights under easement, restriction of the power of grant, the effect of the easement, enjoyment of easement, right of way, the release of easement and termination, while in Nigeria, the easement is implemented by referring to the Land Use Act 1978, Common Law, Doctrines of Equity, Statutes, and court cases. Both countries agreed on the same thing regarding the characteristic of the easement and applied the court ruling in Re Ellenborough Park Case. The characteristic of an easement must consist of a dominant and a servient landowner. Termination of Easement in Malaysia is stated in Sections 289, 290, and 291. In Nigeria, the termination can be done through express release or agreement, merger, or abandonment. Findings from both countries revealed the importance of easement registration as both countries agree that easement should be registered either through a specific form in the land office (Malaysia) or through Prescription, Statutory Grant, Express Grant, Express Reservation, or Implied Grant for Nigeria. The study emphasizes the importance of registering an easement and recommends further research in other court cases in both countries for further understanding.